Synchronization transition in the double dimer model - Wilkins, Neil (2021)
Over the past few decades, interest has grown in classical and quantum phase transitions that cannot be understood in terms of a Landau–Ginzburg–Wilson (LGW) theory. These unconventional transitions, which are often accompanied by other exotic phenomena, such as topological order and confinement of fractionalized excitations, are known to exist in strongly correlated systems such as the dimer model.